Synthesis and reactivity of triphenylstibine-platinum complexes: A bibliographic revision - Barbieri, Roberto Santos; Bellato, Carlos Roberto; Massabni, Antonio Carlos (Soc Brasileira Quimica, 2006)
This article deals with synthesis and reactivity of complexes with triphenylstibine (SbPh3) as the ligand. A comparative study of analogous complexes of triphenylphosphine (PPh3) and triphenylarsine (AsPh3) with platinum in the oxidation states zero, two and four is included. The bibliographic revision includes publications since 1936, when the first Pt(II) complex with triphenylstibine was described.
Keywords: platinum; triphenylstibine; complexes